How to evaluate emerging technologies in cervical cancer screening? - M. Arbyn; Ronco, Guglielmo; Cuzick, Jack; Wentzensen, Nicolas; Castle, Philip E (Int J Cancer, 2009)
Excellent recommendations exist for studying therapeutic and diagnostic questions. We observe that good guidelines on assessment of evidence for screening questions are currently lacking. Guidelines for diagnostic research (STARD), involving systematic application of the reference test (gold standard) to all subjects of large study populations, are not pertinent in situations of screening for disease that is currently not yet present. A five-step framework is proposed for assessing the potential use of a biomarker as a screening tool for cervical cancer: i) correlation studies establishing a trend between the rate of biomarker expression and severity of neoplasia; ii) diagnostic studies in a clinical setting where all women are submitted to verification by the reference standard; iii) biobank-based studies with assessment in archived cytology samples of the biomarker in cervical cancer cases and controls; iv) prospective cohort studies with baseline assessment of the biomarker and monitoring of disease; v) randomised intervention trials aiming to observe reduced incidence of cancer (or its surrogate, severe dysplasia) in the experimental arm at subsequent screening rounds. The 5-phases framework should guide researchers and test developers in planning assessment of new biomarkers and protect clinicians and stakeholders against premature claims for insufficiently evaluated products.
Keywords: Clinical Trials as Topic; Diagnostic Tests, Routine; Female; Humans; Mass Screening; Uterine Cervical Neoplasms